2019
DOI: 10.4103/jmh.jmh_131_18
|View full text |Cite
|
Sign up to set email alerts
|

Appraisal of core therapy, supportive therapy, and alternative therapy in a tertiary care rural hospital of vidarbha region in correlation to plethora of menopausal problems

Abstract: Context: Menopause is a crucial phase of the women fraternity which marks the end of reproductive age. Mostly it is physiological; however, certain conditions may lead to premature menopause. Menopause has an extensive spectrum of symptoms which are extremely bothersome. An effective, empathetic, and rational treatment strategy is necessary. Aim: The present study was carried out to appraise the treatment strategies to tackle menopausal problems in Acharya Vinoba Bhave … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…So, 6 weeks of proper Pilates intervention were programmed [5]. [17][18][19][20]. Few more related were reviewed [21][22][23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…So, 6 weeks of proper Pilates intervention were programmed [5]. [17][18][19][20]. Few more related were reviewed [21][22][23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…Relevant studies on quality of life and supportive therapy were reviewed [18][19][20]. Related issues were addressed in studies of Sharma et al [21][22][23] and Zodpey et al [24][25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…Needs are evident from GBD study data [12][13][14][15][16]. Some of the related articles to various studies in tertiary care hospital were reported [17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%